A 2020 vision for food, agriculture, and environment: the vision, challenge, and recommended action - International Food Policy Research Institute (International Food Policy Research Institute, 1995)
This document builds on past IFPRI research and on analyses and syntheses undertaken as part of the initiative on A 2020 Vision for Food, Agriculture, and the Environment. It is an outcome of extensive discussions within IFPRI and ... a large number of people in government and NGOs, international assistance agencies, academic institutions, national and international agricultural research centers, and the international advisory committee--P. vi.